Significance of concurrent use of weekly cisplatin in carbon‐ion radiotherapy for locally advanced adenocarcinoma of the uterine cervix: A propensity score‐matched analysis. (31st December 2019) - Okonogi, Noriyuki; Wakatsuki, Masaru; Kato, Shingo; Murata, Hiroto; Kiyohara, Hiroki; Karasawa, Kumiko; Ohno, Tatsuya; Tsuji, Hiroshi; Nakano, Takashi; Shozu, Makio; ,
Abstract: Background: Although carbon‐ion radiotherapy (C‐ion RT) with concurrent chemotherapy (chemo‐C‐ion RT) is a promising treatment for adenocarcinoma (AC) of the uterine cervix, its long‐term efficacy remains unclear. We evaluated the long‐term significance of concurrent weekly cisplatin and C‐ion RT for locally advanced AC of the uterine cervix. Methods: We performed a pooled analysis of patients with stage IIB–IVA AC of the uterine cervix who underwent C‐ion RT alone or chemo‐C‐ion RT between September 2007 and December 2018 at our institution. Patients received 74.4 Gy (relative biological effectiveness) with or without cisplatin (40 mg/m 2 per week for up to 5 weeks), underwent no prior pelvic RT or systemic therapy, and had a performance status of 0‐2. Propensity score matching was based on the year of diagnosis, regional lymph node metastasis, and stage. Results: The matched cohort contained 26 patients who underwent C‐ion RT and 26 who underwent chemo‐C‐ion RT. The median age and follow‐up period were 57 (range, 28‐79) years and 34 (range, 2‐126) months, respectively. The 5‐year overall survival rate was significantly better in the chemo‐C‐ion RT group (72%) than in the C‐ion RT group (46%; P  = .041). The 5‐year distant metastatic‐free rate was also significantly better in the chemo‐C‐ion RT group (66%) than in the C‐ion RT group (41%; P  = .048). The incidence of grade ≥ 3 late toxicities was comparable between the two groups. Conclusions: Chemo‐C‐ion RT for locally advanced AC of the uterine cervix is associated with a long‐term survival benefit. Abstract : Chemo‐C‐ion radiotherapy improves survival for uterine cervical adenocarcinoma. Chemo‐C‐ion radiotherapy has improved distant metastatic‐free rates. C‐ion radiotherapy with cisplatin is more effective than C‐ion radiotherapy alone.